Language contact does not drive gesture transfer: Heritage speakers maintain language specific gesture patterns in each language. Issue 2 (30th March 2020) - Azar, Zeynep; Backus, Ad; Özyürek, Aslı
Abstract : This paper investigates whether there are changes in gesture rate when speakers of two languages with different gesture rates (Turkish-high gesture; Dutch-low gesture) come into daily contact. We analyzed gestures produced by second-generation heritage speakers of Turkish in the Netherlands in each language, comparing them to monolingual baselines. We did not find differences between bilingual and monolingual speakers, possibly because bilinguals were proficient in both languages and used them frequently – in line with a usage-based approach to language. However, bilinguals produced more deictic gestures than monolinguals in both Turkish and Dutch, which we interpret as a bilingual strategy. Deictic gestures may help organize discourse by placing entities in gesture space and help reduce the cognitive load associated with being bilingual, e.g., inhibition cost. Therefore, gesture rate does not necessarily change in contact situations but might be modulated by frequency of language use, proficiency, and cognitive factors related to being bilingual.